(3GdefJNH aj Yde GdYjf hYddgG heOGhGJgG HGdCOhjI hGdMOjOs - (3CHh GdbGSe YeGQ Hf Ydj GdehUdj,J (B400 (3g` s ((3YHO GdQMef Hf EHQGgje Hf SGde Hf YeGQ GdCfUGQi GdebOSi GdeJWHH s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdaVd hGdEfYGe hGdehGgH GdYXGe bGd YeGQ deG QCjJ LeGYI ef Cgd UfGYI GdWH ai GdHjeGQSJGfGJ cMGdjf hZjQge eef dGjbQC hdG jcJH ZjQ Cfge jLQHhf Ydi Yjhf GdfGS HJUfja eLehY ef Yde GdYjf hUfGYJgG s
(3BNQgG (B:s
(3MQa Gdeje (B: (3eG ejQGf MGQ ai GdChdi jGHS ai GdKGdKI dg bhI JLdh GdHUQ fTG (B: (3HGQO jGHS hgh eSOO GdhL (B: (3LGQjGHS hGdMeO ddg hMOg s
(3fgGjI GdcJGH HNW eZGjQ cJHJ HYQV GdhQbI (B222 (3GdJi de JJVM GdcJGHI ajgG ef JCKjQ GdQWhHI s
(3hbO cJHgG jhSa Hf YHO GdMcje ef fSNI bOjeIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdWHs